Challenges Encountered by Chinese ESL Learners Problems and Solutions from Complementary Perspectives - Chan, Mable; Benati, Alessandro G. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book provides a blended approach in outlining the properties of grammatical knowledge that have been causing difficulty to Chinese speaking learners, including tense and aspect, articles, passives, unaccusatives, plurality and motion verbs. It explains from different linguistics perspectives how these constraints/difficulties might be dealt with. It also offers readers a comprehensive account of these problems, and outlines the possible pedagogical solutions teachers can try in the classroom. These topics are selected because they bring substantial challenges and difficulties to Chinese English as a Second Language (ESL) learners. This book bridges the gap between acquisition theory and language pedagogy research, benefiting not just language learners but language teachers around the world, and all those who would like to witness collaboration between second language acquisition theory and second language teaching practice in general. It initiates future work in which researchers from different fields with diverging theoretical perspectives and methodological approaches will be able to develop studies that are compatible with each other. This overall can facilitate our understanding of second language acquisition, and how instruction might help. .
Chapter 1. The Acquisition of the English Tense-aspect System by Cantonese ESL Learners -- Chapter 2. The Role of Lexical Aspect in L2 Acquisition of the Present Perfect -- Chapter 3. Systemic Theoretical Instruction and Cognitive Grammar: Acquisition of the English Tense System -- Chapter 4. The Effect of Lexical Aspect on the Use of English Past Marking by Cantonese ESL Learners and its Pedagogical Implications -- Chapter 5. Processing Instruction: Research, Theory and Practical Implications for The Learning and Teaching of English Grammar to Chinese L1 Speakers -- Chapter 6. Not All Unaccusatives are Acquired Equal: Between-Verb Variations in Chinese Learners' Acquisition of English Alternating Unaccusatives -- Chapter 7. Acquisition of English Ditransitives by Mandarin Chinese Learners -- Chapter 8. The Tendencies of Overpassivization and Overuse of Be-Verbs in the Writing of Chinese Learners of English and Applications for Practice -- Chapter 9. Cantonese English as a Second Language (ESL) Learners' and Local English Teachers' Perceived Difficulties of English Article Use and Pedagogical Implications -- Chapter 10. Frequency Effects in Chinese Learners' Acquisition of the English Article Construction -- Chapter 11. Suppliance of Functional Morphology by L1 Chinese L2 English Speakers: The Prosodic Transfer Hypothesis and Pedagogical Implications -- Chapter 12. Factors Affecting Chinese Learners' Acquisition of English Plurality -- Chapter 13. Motion-Path Expressions in L2 English and Pedagogical Implications for Multi-Word Verb Use: A Comparison among Native Speakers of Chinese, Korean, and English.
Keywords: Language and languages-Study and teaching; Education; Language Education; Language Education; Education; Education